World economic outlook. April 2017: gaining momentum? (Washington, DC, 2017)
"Global economic activity is picking up with a long-awaited cyclical recovery in investment, manufacturing, and trade, according to Chapter 1 of this World Economic Outlook. World growth is expected to rise from 3.1 percent in 2016 to 3.5 percent in 2017 and 3.6 percent in 2018. Stronger activity, expectations of more robust global demand, reduced deflationary pressures, and optimistic financial markets are all upside developments. But structural impediments to a stronger recovery and a balance of risks that remains tilted to the downside, especially over the medium term, remain important challenges. Chapter 2 examines how changes in external conditions may affect the pace of income convergence between advanced and emerging market and developing economies. Chapter 3 looks at the trend in the declining share of income that goes to labor and the root causes. Overall, this report stresses the need for credible strategies in advanced economies and emerging market and developing ones to tackle a number of common challenges in an integrated global economy."